Healthcare utilization and spending among older patients diagnosed with Non-Hodgkin lymphoma. Issue 8 (November 2021) - Kenzik, Kelly M.; Williams, Grant R.; Bhakta, Nickhill; Robison, Leslie L.; Landier, Wendy; Goyal, Gaurav; Mehta, Amitkumar; Bhatia, Smita
Abstract: Background: Developing appropriate care models for patients diagnosed with non-Hodgkin lymphoma (NHL) >65y require examination of current healthcare utilization patterns and cost, but non-malignant condition-specific utilization and Medicare spending among older patients has not been characterized. Methods: Using SEER-Medicare, 14, 533 patients diagnosed with NHL at age > 65 between 2008 and 2015 and a comparable non-cancer cohort ( n = 14, 533) were identified. Hospitalizations and outpatient visits for 109 non-malignant conditions were grouped into ten categories, allowing condition-specific utilization and spending calculation from diagnosis to 5y, censoring at blood or marrow transplantation, 6mo prior to death or end (12/31/2016). Using the 90th percentile as a cut-off, factors associated with high-hospitalization rates and high-spending were evaluated. Results: Patients with NHL were 1.5-fold more likely to be hospitalized and 1.8-fold more likely to experience outpatient visits when compared with the non-cancer cohort. Patients with NHL had greater aging-related, cardiovascular, and gastrointestinal hospitalizations than controls ( p < 0.001). Average Medicare spending/visit was higher for patients with NHL (hospitalization: $16, 950 vs. $13, 474, p < 0.001; outpatient: $1176 vs. $392, p < 0.001). Factors associated with high-utilization and high-spending included diffuse large B cell lymphoma subtype, non-white race, and residence in low-education area. Conclusions: Older patients with NHL experienced higher utilization and higher spending per-utilization compared to a non-cancer cohort over five years from cancer diagnosis. Clinical and demographic sub-groups demonstrated increased risk for the highest spending and utilization. The substantial utilization and spending for non-malignant conditions among older patients with NHL provides quantifiable evidence for survivor-adapted healthcare management policies.